2022
DOI: 10.3389/fpls.2022.1043884
|View full text |Cite
|
Sign up to set email alerts
|

Plant leaf veins coupling feature representation and measurement method based on DeepLabV3+

Abstract: The plant leaf veins coupling feature representation and measurement method based on DeepLabV3+ is proposed to solve problems of slow segmentation, partial occlusion of leaf veins, and low measurement accuracy of leaf veins parameters. Firstly, to solve the problem of slow segmentation, the lightweight MobileNetV2 is selected as the extraction network for DeepLabV3+. On this basis, the Convex Hull-Scan method is applied to repair leaf veins. Subsequently, a refinement algorithm, Floodfill MorphologyEx Medianbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…As the essential constituents of the leaves, the leaf veins play a crucial role in transporting assimilates [41]. A recent study found that Camellia oleifera mainly adopts a passive phloem loading mode [23].…”
Section: Regulation Of the Assimilate Transport In Leaves Of Differen...mentioning
confidence: 99%
“…As the essential constituents of the leaves, the leaf veins play a crucial role in transporting assimilates [41]. A recent study found that Camellia oleifera mainly adopts a passive phloem loading mode [23].…”
Section: Regulation Of the Assimilate Transport In Leaves Of Differen...mentioning
confidence: 99%
“…Since the manual measurement of leaf veins is a time-consuming and labor-intensive task, it has been of great interest to automate the process. In recent years, automatic leaf vein segmentation has been performed with classic computer vision approaches [8], [9], [10], [11], traditional machine-learning approaches with hand-crafted feature extraction [12], [13], [14] as well as few deep learning approaches [15].…”
Section: Related Work a Leaf Vein Extraction In Laboratory Settingsmentioning
confidence: 99%